The Evaluation of the Departmental Resources and Positions Within the Inter-Departmental Collaborative Networks: A Case Study on the Joint Prevention and Control Mechanism in China - Yan J (Dove Medical Press, 2023)
Jingjing Yan College of Philosophy, Law & Political Science, Shanghai Normal University, Shanghai, People's Republic of ChinaCorrespondence: Jingjing Yan, College of Philosophy, Law & Political Science, Shanghai Normal University, No. 100 Guilin Road, Shanghai, 200234, People's Republic of China, Email jj.yen@qq.comIntroduction: This study examines the inter-departmental emergency response dynamics within China's Joint Prevention and Control Mechanism (JPCM). Departments' positions in the network are fundamental to understanding the overall structure and operation of the collaborative emergency response. Moreover, understanding the influence of departmental resources on departmental positions promotes efficient inter-departmental collaboration.Methods: The study uses regression analysis to empirically investigate the departmental resources to departments' participation in the JPCM collaboration. The independent variable adopts the departments' positions by statistically presenting the departments' centrality using social network analysis. The dependent variables employ departmental resources, including departmental duties, staffing levels, and approved annual budgets based on data from the government website.Results: The result of social network analysis shows that in JPCM inter-departmental collaboration, the Ministry of Transport, Health Commission, Ministry of Public Security, Ministry of Emergency Management, Ministry of Culture and Tourism, Ministry of Education, and Development and Reform Commission are mainly involved. The regression analysis result indicates that the department's engagement in collaborative actions is determined and influenced by the department's statutory duties. The more statutory duties department has, the more it is in a critical position and role for JPCM.Discussion: The study can assist emergency management practitioners and academic departments in utilizing evidence-based approaches to justify the collaboration and involvement of participating departments. The analysis of the collaborative networks considering JPCM in China by the participation and organization logic is of fundamental significance for arguing for complementing COVID emergency management and inter-departmental emergency collaboration studies.Keywords: Joint Prevention and Control Mechanism, inter-departmental collaboration, COVID, centrality, departmental resources